APPLICATION OF MULTIPOTENT MESENCHYMAL STEM CELL SECRETOME IN THE TREATMENT OF ADJUVANT ARTHRITIS AND CONTACT-ALLERGIC DERMATITIS IN ANIMAL MODELS - P. A. Golubinskaya; M. V. Sarycheva; A. A. Dolzhikov; V. P. Bondarev; M. S. Stefanova; V. O. Soldatov; S. V. Nadezhdin; M. V. Korokin; M. V. Pokrovsky; Yu. E. Burda (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2021)
The therapeutic effect of multipotent mesenchymal stem cells has been proven on various disease models. One of the mechanisms is the paracrine effect of the cells on the surrounding tissues.The aim. To investigate the secretome effectiveness of the multipotent mesenchymal stem cells in the treatment of adjuvant arthritis and contact-allergic dermatitis in Wistar rats.Materials and methods. Adjuvant arthritis was simulated in 26 female rats by the administration of Freund's complete adjuvant and then treated with the administration of 100 µl of multipotent mesenchymal stem cell secretome or saline. Contact-allergic dermatitis was modeled on 30 female rats by applying 200 μl of an oil solution of dinitrofluorobenzene to the skin on days 1, 5 and 6. Then the rats were treated with fluocinolone ointment (a positive control), baby cream (a negative control), baby cream with a secretome of native multipotent mesenchymal stem cells or from the cells processed with dexamethasone.Results. Judging by the indicators of the longitudinal and transverse dimensions of the paws in rats and a histological examination, the secretome did not have any anti-inflammatory effect on adjuvant arthritis. A cream with a secret from multipotent mesenchymal stem cells processed with dexamethasone, was the most effective on the model of contact-allergic dermatitis: the clinical improvement occurred on the 2nd day. The secretome from native multipotent mesenchymal stem cells and fluocinolone had a therapeutic effect on the 3rd day of application, the negative control - on the 4th day. The lymphocytic infiltration coefficient was significantly lower (p <0.05) in all the cases compared to the negative control (2.8 ± 0.1). However, the lowest infiltration was observed when the cream with secretome from native (1.75 ± 0,1) and dexamethasone-stimulated (1.76 ± 0.1) multipotent mesenchymal stem cells was being used.Conclusion. The cream with the secretome of multipotent mesenchymal stem cells suppresses lymphocytic infiltration more strongly than the highly active topical glucocorticosteroid - fluocinolone - on the model of contact-allergic dermatitis, which is a classic local delayed-type hypersensitivity reaction. However, a further study of the therapeutic effect of the secretome on models of systemic inflammatory diseases is required after its preliminary purification from large-molecular proteins.